Review—Recent Trend on Two-Dimensional Metal-Organic Frameworks for Electrochemical Biosensor Application. Issue 13 (28th September 2020) - Ulhakim, Muhamad Taufik; Rezki, Muhammad; Dewi, Kariana Kusuma; Abrori, Syauqi Abdurrahman; Harimurti, Suksmandhira; Septiani, Ni Luh Wulan; Kurnia, Kiki Adi; Setyaningsih, Widiastuti; Darmawan, Noviyan; Yuliarto, Brian
Abstract : Electrochemical biosensors have attracted a tremendous attention for many researchers recently due to its facile synthesis process, tunability easiness by tailoring the material properties or composition, and wide range of biological analyte types detection. To obtain an excellent electrochemical biosensor performance, a material that facilitates fast electron transfer, large surface area, excellent electrocatalytic activity, and abundant available sites for bioconjugation is immensely needed. Metal-organic frameworks in the two-dimensional form (2D MOFs) provide all of the criteria needed as the sensing material for electrochemical biosensors application. However, the design and preparation of 2D MOFs, which have high stability and sensitivity as well as good selectivity for biological analyte detection, is still quite challenging. This review provides the recent studies and development of 2D MOFs as electrochemical biosensor. A detailed discussion about 2D MOFs structures, their synthesis strategy and control, 2D MOFs materials in electrochemical biosensor application, and the future challenges is thoroughly explained in this review. Hopefully, this review will also provide a new inspiration to advance future studies of 2D MOFs materials development as electrochemical biosensor.